Advances in optical imaging for clinical medicine - Iftimia, Nicusor; Brugge, William R.; Hammer, Daniel X. (John Wiley & Sons, 2010)
This book provides students, teachers, researchers and clinicians with a strong and established source of information on advanced optical technologies that show real promise of being translated to clinical use.